El Impacto del Nivel Educativo en el Mercado Laboral Colombiano: Un Análisis de 2012 a 2022 (2024)
This paper provides an overview of the labor market in Colombia, with the objective of evaluating the role of educational level in labor market insertion. The data used were obtained from the annexes published by the National Administrative Department of Statistics (DANE), from which various analyses of labor indicators and demographic variables were carried out. Using tables and graphs, the behavior of these indicators at the national level was examined over time